Strawberry pick tourism marketing strategy in Pancasari Village, Sukasada, Buleleng - Febianti Febianti; Made Widya Paramitha (Institute of Computer Science (IOCS), 2022)
This study shows recommendations on how marketing strategy could be implemented to object researched Pancasari Village that is located in Buleleng Regency, is very potential for farming and agriculture. One of the most popular commodity is strawberry. Along with fast tourism development in Bedugul district, strawberry picking interest more tourist to come. However, there are some evaluation dan development should be taken into consideration, especially in terms of marketing mix (7P), includes product, place, promotion, price, physical evidence, process and people. Hence, it is also needed to evaluate segmenting, targeting, and positioning. This study using qualitative descriptive SWOT analysis and observation with in-depth interview. Results of the study.